Theory of Lodging. (November 2019) - Roberts, Chris; Young, Lisa; Johanson, Misty
For the initial development of the theory of lodging, the focus was on guest behavior in a hotel room. The theory is expanded to encompass the guest behavior in the entire hotel facility, including entrance into the lobby, private usage of the room, and time spent in such areas as the restaurant, lounge, gift shop, gym, spa, function rooms, and so on. The theory began with the observed differences in human behavior while at home versus during an overnight stay at a commercial lodging establishment. Further consideration is given to the guest behavior inside the public spaces of a hotel, which is beyond the privacy of the guest room but still within the protective boundary of the hotel building itself, and which is all a part of the lodging experience.